Evaluating Analyses Trucking Vendor Performance in Covid-19 Vaccine Delivery: A Strategic Assessment Utilizing Analytic Hierarchy Process And Technic For Order Of Preference By Similarity To Ideal Solution Methodologies (Case Study: Indonesian Freight Forwarder’s Role In 2020 Vaccine Shipment) - Sekar Widyastuti Pratiwi; Apsada Juhri; Nursery Alfaridi S. Nasution; Novembriani Irenita; Tenaka Budiman (Dinasti Publisher, 2024)
The purpose of this study was to determine the results of measurements of the priority vendors of the five vendors used by the company in the process of delivery COVID-19 vaccine shipment. This study uses the AHP-TOPSI (Analytic Hierarchy Process – Technic for Order of Preference by Similarity to Ideal Solution) method where the Likert scale is used as a comparison. Problem solving is done by making research using qualitative research methodology with descriptive elaboration. Data collection is done by giving or making questionnaires to get the weight of the assessment carried out by inferring with AHP and Likert from the data collected through questionnaires shared where the respondents came from respondents who have dedication and direct links as well as have the capability to provide vendor performance assessments. The results of the research that were tested from the level of consistency were divided into 5 criteria, namely, Price, Safety, Service, Reliability and Reputation and from the results of the qualitative calculation method by distributing questionnaires from 10 experts for Five existing vendors with adding quantitative approach in TOPSIS, V.2 out as priority vendors.